Strategic research initiative at the Research Techno Plaza - Mhaisalkar, Subodh Gautam. (2008)
With novel synthesis methodologies, new molecules, and atomic scale engineering, tailored properties of materials yielding vastly superior electronic devices and even synthetic body parts seem to be within the realm of possibilities. The Advanced Materials Research Centre is a University-wide research centre that focuses on the synthesis of advanced and innovative functional materials for applications ranging from biotechnology to nanoelectronics. In addition optical, thermal and mechanical characterization of these materials to establish their functionality for the particular application needs to be evaluated. Towards this end, novel techniques for non-contact and wholefield characterization of materials have been developed.